THE IMPORTANCE OF TEACHING VOCABULARY FOR EFL LEARNERS - Bazarbaeva Altinay (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Vocabulary forms the building blocks of language. A strong vocabulary base allows learners to express themselves effectively, understand others, and engage in meaningful conversations